A Decoupling Two-Grid Method for the Steady-State Poisson-Nernst-Planck Equations (Journal of Computational Mathematics, 2019)
Poisson-Nernst-Planck equations are widely used to describe the electrodiffusion ofions in a solvated biomolecular system. Two kinds of two-grid finite element algorithmsare proposed to decouple the steady-state Poisson-Nernst-Planck equations by coarse gridfinite element approximations. Both theoretical analysis and numerical experiments showthe efficiency and effectiveness of the two-grid algorithms for solving Poisson-Nernst-Planckequations.